Інформаційно-технологічна складова у програмах підготовки майбутніх перекладачів в університетах Великобританії - Амеліна, Світлана; Тарасенко, Ростислав (Studies in Comparative Education, 2014)
У статті розглянуто особливості інформаційно-технологічної підготовки майбутніх перекладачів в університетах Великобританії. Встановлено, що переважна більшість британських університетів пропонує програми підготовки перекладачів з акцентом на інформаційно-технологічній складовій. Констатовано, що вона здійснюється шляхом запровадження міждисциплінарних модулів, зміст яких зосереджено на опануванні технологій автоматизованого перекладу та вивченні спеціалізованого програмного забезпечення. Виявлено, що переважна більшість цих модулів передбачає вивчення сучасного стану та розвитку теорії перекладу, різних підходів до обробки тексту й інструментів автоматизованого перекладу. Вказано на можливості імплементації досвіду британських університетів у вітчизняних вищих навчальних закладах. В статье рассмотрены особенности информационно-технологической подготовки будущих переводчиков в университетах Великобритании. Установлено, что подавляющее большинство британских университетов предлагает программы подготовки переводчиков с акцентом на информационно-технологической составляющей. Констатировано, что она осуществляется путем введения междисциплинарных модулей, содержание которых сосредоточено на овладении технологиями автоматизированного перевода и изучении специализированного программного обеспечения. Выявлено, что подавляющее большинство этих модулей предусматривает изучение современного состояния и развития теории перевода, различных подходов к обработке текста и инструментов автоматизированного перевода. Указано на возможности имплементации опыта британских университетов в отечественных высших учебных заведениях. The article deals with features of the information technology training future translators in UK universities. It is found that the vast majority of British universities offer training programs for translators with a focus on information technology component. It is stated that it is carried out by introducing interdisciplinary modules, the content of which is focused on the acquisition of technology-assisted translation and study of specialized software. It is revealed that the vast majority of these modules includes the study of the current state and development of translation theory, different approaches to text processing and automated translation. Students also gain experience with several software products that are constantly used in interpretation and translation and study the requirements for the application of information technology in the translation industry. In addition, students learn how to «sell» their skills in these technologies in the translation services market, and how to use these technologies that could improve their performance in fulfilling their duties and help create a positive reputation in the direct clients and other employers. Students learn to create translation project using software. The implementation possibilities of experience of UK universities in national universities are defined.